On the Parental Influence on Children’s Physical Activities and Mental Health During the COVID-19 Pandemic - Khozaei, Fatemeh; Carbon, Claus-Christian (Frontiers in Psychology, 2022)
Background While neighborhood safety and stranger danger have been mostly canonized to play a part in parents’ physical activity (PA) avoidance, less is known about the impact of parental stress and perceived risk on children’s PA avoidance and consequently on children’s level of PA and wellbeing. Understanding the contributors to children’s wellbeing during pandemic disease is the first critical step in contributing to children’s health during epidemic diseases. Methods This study employed 276 healthy children, aged 10–12 years, and their parents. Data were collected in October and November 2020, about 9 months after the local closing of schools due to the coronavirus disease 2019 (COVID-19) pandemic. Parents and children answered a separate set of questions. Besides the demographic information, the parents responded to questions on their stress level, perceived risk of COVID-19, and PA avoidance for children. Children responded to questions on their PA and wellbeing in the last week. Data were analyzed using SmartPLS and IBM SPSS 22. Results The result of the study supported the four directional research hypotheses of the sequential study model. As hypothesized, parents’ stress and perceived risk levels of COVID-19 negatively affected children’s PA. The PA level was shown to predict children’s wellbeing and mental health. Housing type, parents’ job security, number of siblings, number of members living together in-home, and history of death or hospitalization of relatives or family members due to COVID-19 were found to be associated with parents’ stress and children’s mental health. Conclusion This study sheds light on parents’ role in children’s wellbeing and mental health during the COVID-19 pandemic. Parents with higher stress and high restrictive behaviors might put their children at risk of mental disorders in the end.